2019
DOI: 10.1055/s-0039-1693124
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Reconstruction of High-Flow Cerebrospinal Fluid Leak with Fascia Lata “Button” Graft and Nasoseptal Flap: Surgical Technique and Case Series

Abstract: Background The endoscopic endonasal approach (EEA) has become increasingly used for resection of skull base tumors in the sellar and suprasellar regions. A nasoseptal flap (NSF) is routinely used for anterior skull base reconstruction; however, there are numerous additional allografts and autografts being used in conjunction with the NSF. The role of perioperative cerebrospinal fluid (CSF) diversion is also unclear. Objective This study was aimed to analyze success of high-flow CSF leak repair duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Details of endoscopic endonasal surgery have been described previously ( 25 , 26 ). All surgeries were performed by an endoscopic skull base surgery team comprising a neurosurgeon (D.K.)…”
Section: Methodsmentioning
confidence: 99%
“…Details of endoscopic endonasal surgery have been described previously ( 25 , 26 ). All surgeries were performed by an endoscopic skull base surgery team comprising a neurosurgeon (D.K.)…”
Section: Methodsmentioning
confidence: 99%
“…Among the minor postoperative complications encountered in this study, DI occurred in 13.16% of patients. 14 In another study on 101 patients evaluating the impact of multilayer reconstruction after endoscopic skull base surgery, Simal-Julián et al reported 7 cases of postoperative DI. The surgical technique, which was applied on 32 patients with nonadenomatous sellar pathologies, involved a layer of intradural fat, an epidural layer of fascia lata, and a final layer of vascularized flap.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the risk of CSF leak robust multilayer reconstruction is mandatory-ideally with a combination of fascia lata, nasoseptal flap, and tissue glue in our experience. 38 Special attention must be paid to the anterior margin of the reconstruction as it often has the least amount of normal skull base to adequately appose to. Recent randomized control trials have also proved the efficacy of lumbar drain in decreasing CSF leak secondary to EEAs.…”
Section: Discussionmentioning
confidence: 99%